Vitamin d is associated with a low quality of life: a primary care study - Ebling Brondani, Juliana; Tolazzi Martins, Tamires; Barian, Ana Elize; Vasconcellos Comim, Fabio; Orlandin Premaor, Melissa (Clinical and Biomedical Research, 2023)
Introduction: Some studies have described impairment in quality of life of vitamin- deficient subjects. However, little is known about this association in primary care. This study aimed to evaluate the association between vitamin D deficiency and quality of life in postmenopausal women attending primary care in the municipality of Santa Maria – Brazil. Methods: A cross-sectional study was carried out with postmenopausal women over 55 years of age, accompanied in primary care, from March to August 2014. These women were randomly selected among the participants of a cohort study in the municipality of Santa Maria – Brazil. Data were collected through a standardized questionnaire, quality of life was assessed using the Short Form-36 Health Survey (SF-36), and 25-hydroxyvitamin D were measured using the ALPCO® ELISA method. Results: Of the total of 78 studied women, 11.54% had vitamin D deficiency. Women with vitamin D deficiency had a poorer quality of life assessed by SF-36. In the regression analysis, both vitamin D deficiency and falls were independently associated with a lower physical component of the SF-36.